CD45 functions as a signaling gatekeeper in T cells - Courtney, Adam H; Shvets, Alexey A; Lu, Wen; Griffante, Gloria; Mollenauer, Marianne; Horkova, Veronika; Lo, Wan-Lin; Yu, Steven; Stepanek, Ondrej; Chakraborty, Arup K; Weiss, Arthur (Science signaling, 2019)
T cells require the protein tyrosine phosphatase CD45 to detect and respond to antigen because it activates the Src family kinase Lck, which phosphorylates the T cell antigen receptor (TCR) complex. CD45 activates Lck by opposing the negative regulatory kinase Csk. Paradoxically, CD45 has also been implicated in suppressing TCR signaling by dephosphorylating the same signaling motifs within the TCR complex upon which Lck acts. We sought to reconcile these observations using chemical and genetic perturbations of the Csk/CD45 regulatory axis incorporated with computational analyses. Specifically, we titrated the activities of Csk and CD45 and assessed their influence on Lck activation, TCR-associated ζ-chain phosphorylation, and more downstream signaling events. Acute inhibition of Csk revealed that CD45 suppressed ζ-chain phosphorylation and was necessary for a regulatable pool of active Lck, thereby interconnecting the activating and suppressive roles of CD45 that tune antigen discrimination. CD45 suppressed signaling events that were antigen independent or induced by low-affinity antigen but not those initiated by high-affinity antigen. Together, our findings reveal that CD45 acts as a signaling "gatekeeper," enabling graded signaling outputs while filtering weak or spurious signaling events.
Keywords: CSK Tyrosine-Protein Kinase; Animals; myši transgenní; Receptors, Antigen, T-Cell; Jurkat buňky; Mice, Transgenic; lidé; Mice; signální transdukce; T-lymfocyty; myši; Signal Transduction; receptory antigenů T-buněk; tyrosinkinasa p56(lck), specifická pro lymfocyty; Leukocyte Common Antigens; C-terminální Src kinasa; Lymphocyte Specific Protein Tyrosine Kinase p56(lck); T-Lymphocytes; zvířata; Jurkat Cells; antigeny CD45; Humans